Czterdzieści lat strefowej ochrony gatunków w polskich lasach Część 1. Zagadnienia prawne - Referowska, Ewa (Leśne Prace Badawcze, 2025)
The main aim of this series of articles is to present the multiplicity and complexity of aspects and problems accompanying the implementation of zonal species protection in Polish forests from 1983 to 2024, which may be helpful for its further improvement. This publication, the first in the series, aims to address the legal issues of the functioning concerning protection zones in forests. The research methodology is consistent throughout the entire series. A review of legislation from 1983 to 2024, a systematic literature review, and the snowball method were used. The systematic literature review for the period 1984-2023 was carried out using the bibliographic database of the Forest Research Institute (keywords: ‘ochron* strefow*’, ‘stref* ochron*’) and the SCOPUS database (keywords: ‘zonal protection’ AND ‘Poland’; ‘zone protection’ AND ‘Poland’). From the results obtained (483 items), after further selection (Fig. 1), 28 publications were selected, used to varying extents in the individual parts of the article series (Appendix 1); in this article, 22 of these were used. Together with the literature items identified through the snowball method, these publications were thoroughly examined with regard to the aspects and issues of zonal protection in forests discussed within them. This article addresses issues such as the legal establishment of protection zones in forests, restrictions imposed on these areas for humans and forest management introduced to meet the needs of zonal species protection, the marking of zones, the of their removal, the protection of sensitive environmental data, and the problem of non-compliance with the law by both forest managers and the general public. It presents the evolution of approaches and adopted solutions to individual problems over 40 years of the functioning of the discussed form of nature protection, resulting from the simultaneous evolution of the knowledge about species, but also about the political-administrative-economic changes that have taken place in Poland during that period, as well as changes in the awareness of people involved in zonal protection. Due to the fact that there are still legal areas indicated in this article which require correction, clarification, or more effective implementation (for example, regarding zone liquidation, their marking, unification of procedures, interpretation of the law, and law enforcement), it would be advisable in the near future to consider solutions to improve these aspects so that zonal protection is unambiguous and precise. This is important for its natural effectiveness and public acceptance.